Infiltration of central nervous system in adult acute myeloid leukaemia. Issue 6158 (27th January 1979) - Pippard, M J; Callender, S T; Sheldon, P W
Abstract : Out of 64 consecutive unselected patients with acute myeloid leukaemia studied during 1973-6, five developed clinical evidence of spread to the central nervous system (CNS). Neuroradiological examination showed cerebral deposits in three, in whom rapid symptomatic relief was obtained with radiotherapy. In two of these patients who developed solid intracranial deposits haematological remission could be reinduced or maintained; they were still alive 86 and 134 weeks later. When patients presented with spread to the CNS complicating generalised uncontrolled leukaemia they had short survivals. CNS infiltration may respond dramatically to appropriate treatment provided that it is not associated with generalised uncontrolled leukaemia, which has a poor prognosis. In view of this, routine "prophylaxis" of the CNS in adult acute myeloid leukaemia does not seem justified at present.